Effect of Long-Term Supplementation With Silkworm Pupae Oil on the Methane Yield, Ruminal Protozoa, and Archaea Community in Sheep - Thirumalaisamy, Govindasamy; Malik, Pradeep Kumar; Trivedi, Shraddha; Kolte, Atul Purushottam; Bhatta, Raghavendra (Frontiers in Microbiology, 2022)
Supplementation with lipids and oils is one of the most efficient strategies for reducing enteric methane emission. However, high costs and adverse impacts on fiber degradation restrict the use of conventional oils. Silkworm pupae, a non-conventional oil source rarely used for human consumption in India, could be one of the cheaper alternatives for methane mitigation. The objective of this study was to investigate the effect on sheep of long-term supplementation (180 days) of silkworm pupae oil (SWPO) with two distinct supplementation regimes (daily and biweekly) on daily enteric methane emission, methane yield, nutrient digestibility, rumen fermentation, ruminal archaea community composition, and protozoal population. The effect of the discontinuation of oil supplementation on enteric methane emission was also investigated. Eighteen adult male sheep, randomly divided into three groups (n = 6), were provisioned with a mixed diet consisting of 10.1% crude protein (CP) and 11.7 MJ/kg metabolizable energy formulated using finger millet straw and concentrate in a 55:45 ratio. SWPO was supplemented at 2% of dry matter intake (DMI) in test groups either daily (CON) or biweekly (INT), while no oil was supplemented in the control group (CTR). DMI (p = 0.15) and CP (p = 0.16) in the CON and INT groups were similar to that of the CTR group; however, the energy intake (MJ/kg) in the supplemented groups (CON and INT) was higher (p < 0.001) than in CTR. In the CON group, body weight gain (kg, p = 0.02) and average daily gain (g, p = 0.02) were both higher than in the CTR. The daily methane emission in the CON (17.5 g/day) and INT (18.0 g/day) groups was lower (p = 0.01) than the CTR group (23.6 g/day), indicating a reduction of 23–25% due to SWPO supplementation. Similarly, compared with the CTR group, methane yields (g/kg DMI) in test groups were also significantly lower (p < 0.01). The transient nature of the anti-methanogenic effect of SWPO was demonstrated in the oil discontinuation study, where daily methane emission reverted to pre-supplementation levels after a short period. The recorded methanogens were affiliated to the families Methanobacteriaceae, Methanomassilliicoccaceae, and Methanosarcinaceae. The long-term supplementation of oil did not induce any significant change in the rumen archaeal community, whereas minor species such as Group3b exhibited differing abundance among the groups. Methanobrevibacter, irrespective of treatment, was the largest genus, while Methanobrevibacter gottschalkii was the dominant species. Oil supplementation in CON and INT compared with CTR decreased (p < 0.01) the numbers of total protozoa (× 107 cells/ml), Entodiniomorphs (× 107 cells/ml), and Holotrichs (× 106 cells/ml). SWPO continuous supplementation (CON group) resulted in the largest reduction in enteric methane emission and relatively higher body weight gain (p = 0.02) in sheep.